Enhancement of microhomology-mediated genomic rearrangements by transient loss of mouse Bloom syndrome helicase - Yamanishi, Ayako; Yusa, Kosuke; Horie, Kyoji; Tokunaga, Masahiro; Kusano, Kohji; Kokubu, Chikara; Takeda, Junji (Genome Research, 2013)
Bloom syndrome, an autosomal recessive disorder of the BLM gene, confers predisposition to a broad spectrum of early-onset cancers in multiple tissue types. Loss of genomic integrity is a primary hallmark of such human malignancies, but many studies using disease-affected specimens are limited in that they are retrospective and devoid of an appropriate experimental control. To overcome this, we devised an experimental system to recapitulate the early molecular events in genetically engineered mouse embryonic stem cells, in which cells undergoing loss of heterozygosity (LOH) can be enriched after inducible down-regulation of Blm expression, with or without site-directed DNA double-strand break (DSB) induction. Transient loss of BLM increased the rate of LOH, whose breakpoints were distributed along the chromosome. Combined with site-directed DSB induction, loss of BLM synergistically increased the rate of LOH and concentrated the breakpoints around the targeted chromosomal region. We characterized the LOH events using specifically tailored genomic tools, such as high-resolution array comparative genomic hybridization and high-density single nucleotide polymorphism genotyping, revealing that the combination of BLM suppression and DSB induction enhanced genomic rearrangements, including deletions and insertions, whose breakpoints were clustered in genomic inverted repeats and associated with junctional microhomologies. Our experimental approach successfully uncovered the detailed molecular mechanisms of as-yet-uncharacterized loss of heterozygosities and reveals the significant contribution of microhomology-mediated genomic rearrangements, which could be widely applicable to the early steps of cancer formation in general.